Bank credit allocation and productivity stylised facts for Portugal - Azevedo, Nuno (2022)
With a dataset covering 95% of total outstanding credit to non-financial corporations recorded in the Portuguese credit register, we investigate whether outstanding loans by resident banks to 64 economic sectors have been granted to the most productive firms. We find evidence of misallocation, which reflects the joint effects of credit supply and credit demand decisions taken over the course of time, and the adverse cyclical developments following the accumulation of imbalances in the Portuguese economy for a protracted period. In 2008-2016, the share of outstanding credit granted to firms with very low productivity (measured or inferred) was always substantial, peaking at 44% in 2013, and declining afterwards with the rebound in economic activity and the growing allocation of new loans towards lower risk firms and away from higher risk firms. Furthermore, we find that misallocation is associated with slower reallocation. The responsiveness of credit growth to firm relative productivity is much lower in sectors with relatively more misallocated credit and when banks have a high share of such credit in their portfolios.